Analysis of Product Innovation and Customer Relationship Management (CRM) as Marketing Tools by UMKM Sawo Sukatali - Kartiwa, Aa; Az Zahra, Syifa Deliasari; Febriyanti, Aliya Susilo; Muharam, Anggun Nur Riska Muharam; Ariska, Siti (SINTESA, 2024)
The study analyzes the role of product innovation and Customer Relationship Management (CRM) in enhancing the competitiveness of Sawo Sukatali SMEs in Sumedang Regency, using a qualitative approach through interviews, observations, and documentation. Sawo Sukatali SMEs have significant potential but face challenges in product innovation, competitiveness, and marketing effectiveness. The findings show that Sawo Sukatali SMEs have successfully innovated by creating various processed sawo products such as syrup, chips, dodol, and cakes, which add value and market appeal. The implementation of CRM has also enchanced customer loyalty through personalized services and operational efficiency. The main challenges include decining demand due to the pandemic and limit ed product distribution. Consumers show strong preferences for high-quality products, attractive packaging, and excellent service, highlighting the importance of innovation and CRM in creating positive customer experiences. Overall Sawo Sukatali SMEs have seccessfully empowered local potential through product innovation and CRM implementation, providing inspiration for other SMEs to continue innovating and leveraging their regional strengths